Dimensi Sosial dalam Tafsir Sufistik - Aty Munshihah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
Faiḍ ar-Rahmān fī Tarjama Tafsīr Kalam Malik ad-Dayyān by KH. Shaleh Darat land has been read from a sufitic dimension. However, there is actually a social dimension that has escaped the previous readings. Therefore, this study provides a new perspective in reading the interpretation of KH. Soleh Darat especially in QS. al-Fatihah [1]: 1. This type of research is classified as library research . By using a contextual-sufistic approach, the results of this study are; first , the two characteristics that are in the basmalah pronunciation not only show attributes for Allah but also humans; second , basmalah have social value in it, h al it is illustrated by their compassionate nature that also must be inculcated in ourselves humans themselves (both physical and spiritual) and then applied to the fellow beings by sharing sustenance and mutual reminded in his favor; third, the practice of social life as a symbol that there is God as the Creator.